Review and Comparison of the Models for Asset Pricing with Empirical Evidence from UK Stock Market - Tam, Ka Tung (2007)
This study aims to provide a review and comparison of three noticeable models for asset pricing including classic CAPM, Fama-French Three-Factor Model and Liquidity-adjusted CAPM from the empirical evidence of UK stock market. By adopting the methodology of Fama and MacBeth (1973) and testing five years data of 494 companies in FTSE All-share Index, the research finds that both CAPM and FF model are not robust enough to explain expected return and FF model performs slightly better the CAPM. Although the market factor is significant, market beta has no explanation power. LCAPM, an augmented version of CAPM, can be constructed by several ways. Although the one being tested is only a simplified version, it is still more robust than classic CAPM and FF model. Stock liquidity is found to significant to expected return, book-to-market ratio comes the second and size factor is irrelevant. The study also attempts to build a hybrid model by combining the three significant factors comprising market, book-to-market ratio and liquidity. Yet, it is rejected as no improvement can be seen. Finally the study further discusses some issues such as death of beta, limitations of research etc.